Presidential Address: Does Monetary Policy Matter? The Narrative Approach after 35 Years - Romer, Christina D.; Romer, David H. (American Economic Review, 2023)
The narrative approach to macroeconomic identification uses qualitative sources, such as newspapers or government records, to provide information that can help establish causal relationships. This paper discusses the requirements for rigorous narrative analysis using fresh research on the impact of monetary policy as the focal application. We read the historical Minutes and Transcripts of Federal Reserve policymaking meetings to identify significant contractionary and expansionary changes in monetary policy not taken in response to current or prospective developments in real activity for the period 1946 to 2016. We find that such monetary shocks have large and significant effects on unemployment, output, and inflation in the expected directions. Analysis of available policy records suggests that a contractionary monetary shock likely occurred in 2022. Based on the empirical estimates of the effect of previous shocks, one would expect substantial negative impacts on real GDP and inflation in 2023 and 2024. (JEL E31, E52, E58, E65, N12)